Leveraging synergy of SDWN and multi‐layer resource management for 5G networks. Issue 5 (1st September 2018) - Derakhshani, Mahsa; Parsaeefard, Saeedeh; Le‐Ngoc, Tho; Leon‐Garcia, Alberto
Abstract : Fifth‐generation (5G) networks are envisioned to predispose flexible edge‐to‐core infrastructure to offer diverse applications. Convergence of software‐defined networking, software‐defined radio, and virtualisation on the concept of software‐defined wireless networking (SDWN) is a promising approach to support such dynamic networks. The principal technique behind the 5G‐SDWN framework is the separation of control and data planes that allows the abstraction of resources as transmission parameters of users. In such environment, resource management plays a critical role to achieve efficiency and reliability. The authors introduce a converged multi‐layer resource management (CML‐RM) framework for SDWN‐enabled 5G networks that involve a functional model and an optimisation framework. In such framework, the key questions are if 5G‐SDWN can be leveraged to enable CML‐RM over the portfolio of resources, and reciprocally, if CML‐RM can effectively provide performance enhancement and reliability for 5G‐SDWN. The authors tackle these questions by proposing a flexible protocol structure for 5G‐SDWN, which can handle all the required functionalities in a more cross‐layer manner. They demonstrate how the proposed general framework of CML‐RM can control the end‐user quality of experience. Moreover, for two scenarios of 5G‐SDWN, they investigate the effects of joint user‐association and resource allocation via CML‐RM to improve performance in virtualised networks.